An approach to automatic boundary segmentation of solid models using virtual topology: toward reconstruction of design features. Issue 3 (7th April 2020) - Zhang, Yingzhong; Fu, Yufei; Jia, Jia; Luo, Xiaofang
Abstract: Boundary segmentation of solid models is the geometric foundation to reconstruct design features. In this paper, based on the shape evolution analysis for the feature-based modeling process, a novel approach to the automatic boundary segmentation of solid models for reconstructing design features is proposed. The presented approach simulates the designer's decomposing thinking on how to decompose an existing boundary representation model into a set of design features. First, the modeling traces of design features are formally represented as a set of feature vertex adjacent graphs that use low-dimensional vertex entities and their connection relations. Then, a set of Boolean segmentation loops is searched and extracted from the constructed feature vertex adjacent graphs, which segment the boundary of a solid model into a set of regions with different design feature semantics. In the search process, virtual topology operations are employed to simulate the topological changes resulting from Boolean operations in feature modeling processes. In addition, to realize effective search, search strategies and search algorithms are presented. The segmentation experiments and case study show that the presented approach is feasible and effective for the boundary segmentation of medium-level complex part models. The presented approach lays the foundation for the later reconstruction of design features. Graphical Abstract: